1988
DOI: 10.1007/bf00130932
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous collection of particles and gases followed by multielement analysis using nuclear techniques

Abstract: A simple system was constructed for the separation and collection of atmospheric particles and gases. The five-stage sampling train consists of a particle filter followed by four 7 LiOHimpregnated filters to collect acidic gases. The treated filters quantitatively collect acidic gas-phase species of B, S, CI, Br, I, As, Se, Sb and Hg. Simultaneous sampling with activated charcoalimpregnated and 7 LiOH-treated filters revealed that B, S, and As species were found only as acidic gases, while the others had both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 29 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…Forty-eight gas and aerosol samples were collected during December 1986December , 1988December , 1989, and January 1991 using custom-made 110 mm and Nuclepore 47 mm filter packs [Finnegan et al 1989;Kitto et al, 1988]. The packs consist of a particulate filter (one of the following filters were used: Fluoropore (1.0 tim), Zefluor (2.0 ttm), and Sartorius (1.2 ttm) teflon (PTFE) or Nuclepore polycarbonate aerosol (0.4 ttm)) followed by two or more impregnated filters.…”
Section: Samples and Analytical Techniquesmentioning
confidence: 99%
“…Forty-eight gas and aerosol samples were collected during December 1986December , 1988December , 1989, and January 1991 using custom-made 110 mm and Nuclepore 47 mm filter packs [Finnegan et al 1989;Kitto et al, 1988]. The packs consist of a particulate filter (one of the following filters were used: Fluoropore (1.0 tim), Zefluor (2.0 ttm), and Sartorius (1.2 ttm) teflon (PTFE) or Nuclepore polycarbonate aerosol (0.4 ttm)) followed by two or more impregnated filters.…”
Section: Samples and Analytical Techniquesmentioning
confidence: 99%
“…Efficiency calibration was performed using a National Bureau of Standards, Standard Reference Material 4275 mixed radionuclide source. Previous experiments with activated charcoal [5] have shown that the acidic fraction, probably as HI, constitutes the majority (~70%) of the gaseous iodine. Organic iodide gases are not retained on the base-treated filters.…”
Section: Methodsmentioning
confidence: 99%
“…A complete description of the air sampling technique was described previously by Kitto et al [5]. In brief, 1 ambient air was drawn through an 11.0 cm 5-stage filter holder with a 1 μηι pore-size Fluoropore particlecollecting filter as the first stage.…”
Section: Methodsmentioning
confidence: 99%
“…To assess the dangerous characteristics of radioactive iodine, detailed knowledge of the behavior of iodine in the environment is required; the behavior is influenced by the concentration of water in the air and by atmospheric conditions. The background iodine concentration is at a level of a few nanograms per cubic meter, and a large amount of this atmospheric iodine exists as gaseous compounds like elementary iodine, hypoiodous acid, hydrogen iodide, and methyl iodide [10]. However, a distinct amount of atmospheric iodine also exists in a particulate iodine state [11], and the distribution of iodine species in aerosol particles is relatively unknown.…”
Section: Introductionmentioning
confidence: 99%